(untitled) (Research, Society and Development, 2023)
Practices of Permanent Education in Health (EPS) can be seen as strategies to strengthen learning in the way of providing health care based on the appreciation of professional experiences. This article aims to describe the protocol of a study to implement an EPS practice in a teaching hospital. This is a quasi-experimental study, which proposes offering a practice to strengthen EPS called multidisciplinary learning groups (GMA). Six GMA will be offered per participant, at monthly intervals. Each GMA will consist of moments: warm-up, stimulus to critical thinking/problematization and awareness. Reflective discussions and asynchronous information (AI) will take place between meetings. The AI ​​consist of videos with technical information, based on reports and experiences of the professionals, with the themes discussed in the GMA, to establish learning. For the implementation, the execution plan will be elaborated, which will be submitted to the evaluation method of judges, followed by the offer of the intervention. The evaluation of the implementation of the GMA will occur through the measurement of institutional indicators, related to clinical management, in the pre- and post-implementation periods. Also, there will be interviews with the participants, with the purpose of evaluating the contributions of participation in the groups for professional practices. It is expected that the implementation of the GMA will contribute to the exchange of experiences, translation of scientific technical knowledge and qualification of the care offered, in addition to strengthening the EPS practice in the institution, applicable in other places.